Transition metal doped three-dimensional hybrid zeolite imidazole framework photo-thermal material and preparation method thereof

By introducing transition metal ions into the three-dimensional hybrid zeolite imidazole frame, the one-step solvothermal method is used to solve the problems of narrow light absorption range and poor photothermal conversion performance of photothermal materials, achieving efficient photothermal conversion performance and low-cost preparation.

CN119285967AActive Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411022512.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-10
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

The existing photothermal materials have narrow light absorption range, poor photothermal conversion performance, high production cost and cumbersome process.

Method used

By adopting a one-step solvothermal method, the energy band structure is adjusted, the light absorption range is broadened and the photothermal conversion performance is improved by introducing transition metal ions (Cu2+, Co2+, Ni2+, Mn2+) into the three-dimensional hybrid zeolite imidazole frame.

Benefits of technology

The excellent photothermal conversion performance of photothermal materials is achieved, and the introduction of additional photothermal conversion modules of doped metal ions improves the stability and photothermal performance of the material, and reduces the preparation cost and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285967A_ABST
    Figure CN119285967A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a transition metal doped three-dimensional hybrid zeolite imidazole framework photo-thermal material, 2-methylbenzimidazole is selected as a ligand connector, and the structure of the 2-methylbenzimidazole has a high conjugation effect, so that the improvement of photo-thermal performance is facilitated; secondly, transition metal ions are introduced into a three-dimensional hybrid zeolite imidazole framework to change an energy band structure of the framework, so that the light absorption range of the material is widened, an additional photo-thermal conversion module can be introduced through intrinsic d-d transition of the transition metal ions, and the photo-thermal performance of the material is further improved. The method is simple and easy to operate, the product purity is high, the crystallinity is good, the agglomeration phenomenon is few, and crystal particles with good dispersity can be obtained easily. The test result shows that the transition metal ions are successfully doped into the HZIF-3 frame, and the photo-thermal performance is improved by 5-8 DEG C compared with that of the HZIF-3 powder material without doping the transition metal ions on the basis of not changing the original morphology of the crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of MOF-based photothermal materials, and specifically relates to a method for preparing a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material, and also relates to a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material. Background Art

[0002] With the increase in population and the impact of climate change, global freshwater resources are gradually decreasing, while seawater reserves are abundant. Therefore, producing fresh water using seawater as raw material is one of the effective ways to alleviate water scarcity. In recent years, interfacial solar water evaporation systems have attracted much attention due to their low cost and high efficiency. As one of the most important components in interfacial solar water evaporation systems, photothermal materials are directly related to the absorption of solar energy and directly determine the evaporation performance of the evaporator. Metal-organic framework materials (MOFs) are self-assembled by metal ions or metal clusters and organic ligands through coordination. Their structure is highly designable and controllable. The pore size, shape and function can be adjusted by selecting different metal centers and organic ligands, thereby optimizing the absorption of light and heat conversion efficiency. Among them, the hybrid zeolite imidazole framework (HZIF) is a novel metal-organic framework that introduces zeolite-like inorganic tetrahedral metal oxoate TO4 into the crystal structure of the zeolite-type metal imidazole framework, synthesizing a hybrid crystalline three-dimensional framework between ZIF and inorganic zeolite, which combines the advantages of high stability and structural designability of both, and the framework is endowed with unique physicochemical properties due to the introduction of high-valent metals. In addition, doping foreign metal ions into the Zn(II) nodes of HZIF can introduce new electronic energy levels into the energy band of HZIF to form inter-band trap sites, which is beneficial to broaden their light absorption range and reduce electron-hole recombination. It can also bring many benefits. For example: (1) The band structure of MOF can be adjusted, thereby broadening their light absorption range; (2) doped metal ions (e.g., Co 2+ and Cu 2+ )’s intrinsic dd transition can introduce additional photothermal conversion modules; (3) a new metal-metal charge transfer (MMCT) mode is introduced to improve the separation efficiency of photogenerated electron-hole pairs; (4) metal ion doping can also improve the stability of MOF.

[0003] At present, the preparation cost of some photothermal materials is high and the process is complicated. In view of the above two points, this experiment uses a one-step solvothermal method to synthesize a photothermal material with better performance. Summary of the invention

[0004] The first objective of the present invention is to provide a method for preparing a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material, which solves the problems of narrow light absorption range and poor photothermal conversion performance of the photothermal material.

[0005] The second object of the present invention is to provide a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material.

[0006] The first technical solution adopted by the present invention is a method for preparing a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material, and the specific operating steps are as follows:

[0007] Step 1, weigh a certain amount of zinc citrate dihydrate, molybdic acid and 2-methylbenzimidazole, dissolve them in N,N-dimethylformamide (DMF) solution, and stir them thoroughly to obtain solution A.

[0008] Step 2: weigh a certain amount of metal acetate (copper acetate, cobalt acetate, nickel acetate, manganese acetate) and add them to solution A respectively, mix and stir to obtain solutions containing different transition metal ions (Cu 2+ 、Co 2+ 、Ni 2+ , Mn 2+ ) of solution B.

[0009] Step 3, the solution B obtained in step 2 is transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven with a programmed cooling function, and the temperature is adjusted to 160° C. for 72 hours.

[0010] Step 4, after the reactor is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing, and the product is in the form of blue-black blocks.

[0011] Step 5, placing the product obtained by filtration into a 60° C. vacuum drying oven, drying for 12 h, and dry grinding to obtain a blue-black powder.

[0012] The present invention is also characterized in that:

[0013] In step 1, the molar ratio of zinc citrate dihydrate to molybdic acid and 2-methylbenzimidazole is 1:11:6.

[0014] In step 1, the ratio of the total mass of zinc citrate dihydrate, molybdic acid, and 2-methylbenzimidazole to N,N-dimethylformamide is 0.65-0.7 g: 5-8 mL.

[0015] The stirring time in step 1 is 20-60 min.

[0016] In step 2, the molar ratio of metal acetate to zinc citrate dihydrate is 1:3.

[0017] In step 2, the metal acetate can be replaced by nitrate, chloride or the like.

[0018] The heating rate of the oven in step 3 is 3-5°C / min. In the case of an oven without programmed cooling, an ordinary oven can be used instead. When cooling, turn off the power of the oven and let it naturally cool to room temperature.

[0019] The setting range of the oven temperature in step 3 is 140-180° C., and the time range is 60-80 h.

[0020] In step 4, DMF solution is used for suction filtration and washing operation.

[0021] In step 4, ultrasonic treatment can be performed before filtration and washing to remove the precipitate attached to the surface of the crystal.

[0022] The temperature range of the vacuum drying oven in step 5 is 40-80° C., and the time range is 8-20 h.

[0023] The second technical solution adopted by the present invention is to prepare the photothermal material using the preparation method of the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention adopts a simple one-step solvothermal method to transfer the mixed drugs to a hydrothermal reactor under a high temperature and high pressure reaction environment to synthesize a three-dimensional hybrid zeolite imidazole framework material doped with transition metal ions. The framework has multiple metal active sites, and the high conjugation effect of the ligand makes the material have relatively excellent photothermal conversion performance.

[0026] (2) The photothermal material prepared by the present invention exhibits excellent photothermal conversion performance under the irradiation of a xenon lamp light source. The xenon lamp light source is adjusted to one sun intensity for photothermal performance testing, wherein the transition metal Cu doped 2+ The maximum average surface temperature of the sample reached 90℃ after 10 minutes of illumination.

[0027] (3) The present invention is to dope transition metal ions (Cu) during the synthesis process. 2+ 、Co 2+ 、Ni 2+ , Mn 2+ ) thus the Zn 2+ The sites are replaced to achieve the regulation of the crystal structure and improve the photothermal performance of the material. This method can also be tried with other Zn 2+ Doping with isostructural transition metal ions is an extended synthesis strategy. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of the preparation method of the transition metal ion-doped hybrid zeolite imidazole framework photothermal material of the present invention;

[0029] Figure 2 The transition metal Cu in the present invention 2+ XRD diffraction pattern of doped hybrid zeolite imidazole framework photothermal material;

[0030] Figure 3 The transition metal Cu of the present invention 2+ SEM image of doped hybrid zeolite imidazole framework photothermal material.

[0031] Figure 4 The transition metal Cu of the present invention 2+ Surface infrared image of the doped hybrid zeolite imidazole framework photothermal material irradiated for 800s under one sun intensity;

[0032] Figure 5 The transition metal Cu of the present invention 2+ Temperature curve of the doped hybrid zeolite imidazole framework photothermal material irradiated with one sun intensity for 800s;

[0033] Figure 6 The transition metal Cu of the present invention 2+ Cyclic curve of the doped hybrid zeolite imidazole framework photothermal material after 10 irradiations at one sun intensity.

[0034] Figure 7 The transition metal Cu of the present invention 2+ Absorption diagram of doped hybrid zeolite imidazole framework photothermal material in the ultraviolet, visible and near-infrared regions. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0036] The purpose of the present invention is to introduce transition metal ions (Cu) into the process of synthesizing HZIF-3. 2+ 、Co 2+ 、Ni 2+ , Mn 2+ ) to obtain a three-dimensional hybrid zeolite imidazole framework photothermal material doped with transition metal ions. Compared with the traditional solid-phase synthesis method, the solvent thermal method can omit the calcination and grinding steps, reduce the possibility of powder contamination, and improve the purity and crystal integrity of the product. This method can adjust the reaction environment atmosphere so that each ion can be evenly doped in the crystal framework. In addition, the intrinsic dd transition of the doped metal ions can introduce additional photothermal conversion modules, promote the transfer rate between electrons, and further improve the photothermal performance of the material. Finally, through the processes of filtration, washing, drying, etc., a three-dimensional hybrid zeolite imidazole framework photothermal powder material doped with transition metal ions is finally obtained.

[0037] The present invention will be further described below in conjunction with specific embodiments.

[0038] Example 1

[0039] The preparation method of the transition metal ion doped three-dimensional hybrid zeolite imidazole framework photothermal powder material of the present invention is as follows Figure 1 The specific steps are as follows:

[0040] Step 1, weigh 0.122 g (0.2 mmol) of zinc citrate dihydrate, 0.38 g (2.117 mmol) of molybdic acid and 0.158 g (1.196 mmol) of 2-methylbenzimidazole, dissolve in 5 mL of N,N-dimethylformamide (DMF) solution, and stir well to obtain solution A.

[0041] Step 2: weigh 0.013 g (0.067 mmol) of copper acetate and add it to solution A, stirring thoroughly to obtain a solution containing transition metal Cu. 2+ of solution B.

[0042] Step 3, transfer the solution B in step 2 to a stainless steel reactor lined with polytetrafluoroethylene, put it in an oven with a programmed cooling function, set the temperature to 160°C, and the time to 72 hours.

[0043] Step 4, after the reaction kettle is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing with DMF solution, and the product is in the form of blue-black blocks.

[0044] Step 5, placing the product obtained by filtration into a 60° C. vacuum drying oven, drying for 12 h, and dry grinding to obtain a blue-black powder.

[0045] Example 2

[0046] Step 1, weigh 0.122 g (0.2 mmol) of zinc citrate dihydrate, 0.38 g (2.117 mmol) of molybdic acid and 0.158 g (1.196 mmol) of 2-methylbenzimidazole, dissolve in 5 mL of N,N-dimethylformamide (DMF) solution, and stir well to obtain solution A.

[0047] Step 2: weigh 0.017 g (0.067 mmol) of cobalt acetate and add it to solution A, and stir thoroughly to obtain a solution containing transition metal Co. 2+ of solution B.

[0048] Step 3, transfer the solution B in step 2 to a stainless steel reactor lined with polytetrafluoroethylene, put it in an oven with a programmed cooling function, set the temperature to 160°C, and the time to 72 hours.

[0049] Step 4, after the reaction kettle is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing with DMF solution, and the product is in the form of blue-black blocks.

[0050] Step 5, placing the product obtained by filtration into a 50° C. vacuum drying oven, drying for 16 h, and dry grinding to obtain a blue-black powder.

[0051] Example 3

[0052] Step 1, weigh 0.122 g (0.2 mmol) of zinc citrate dihydrate, 0.38 g (2.117 mmol) of molybdic acid and 0.158 g (1.196 mmol) of 2-methylbenzimidazole, dissolve in 5 mL of N,N-dimethylformamide (DMF) solution, and stir well to obtain solution A.

[0053] Step 2: weigh 0.017 g (0.067 mmol) of nickel acetate and add it to solution A, stirring thoroughly to obtain a transition metal Ni 2+ of solution B.

[0054] Step 3, transfer the solution B in step 2 to a stainless steel reactor lined with polytetrafluoroethylene, put it in an oven with a programmed cooling function, set the temperature to 160°C, and the time to 72 hours.

[0055] Step 4, after the reaction kettle is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing with DMF solution, and the product is in the form of blue-black blocks.

[0056] Step 5, placing the product obtained by filtration into a 60° C. vacuum drying oven, drying for 12 h, and dry grinding to obtain a blue-black powder.

[0057] Example 4

[0058] Step 1, weigh 0.122 g (0.2 mmol) of zinc citrate dihydrate, 0.38 g (2.117 mmol) of molybdic acid and 0.158 g (1.196 mmol) of 2-methylbenzimidazole, dissolve in 5 mL of N,N-dimethylformamide (DMF) solution, and stir well to obtain solution A.

[0059] Step 2: weigh 0.016 g (0.067 mmol) of manganese acetate and add it to solution A, and stir thoroughly to obtain a solution containing transition metal Mn. 2+ of solution B.

[0060] Step 3, transfer the solution B in step 2 to a stainless steel reactor lined with polytetrafluoroethylene, put it in an oven with a programmed cooling function, set the temperature to 160°C, and the time to 72 hours.

[0061] Step 5, after the reaction kettle is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing with DMF solution, and the product is in the form of blue-black blocks.

[0062] Step 6, placing the product obtained by filtration into a 60° C. vacuum drying oven, drying for 12 h, and dry grinding to obtain a blue-black powder.

[0063] Example 5

[0064] Step 1, weigh 0.122 g (0.2 mmol) of zinc citrate dihydrate, 0.38 g (2.117 mmol) of molybdic acid and 0.158 g (1.196 mmol) of 2-methylbenzimidazole, dissolve in 7 mL of N,N-dimethylformamide (DMF) solution, and stir well to obtain solution A.

[0065] Step 2: weigh 0.013 g (0.067 mmol) of copper acetate and add it to solution A, stirring thoroughly to obtain a solution containing transition metal Cu. 2+ of solution B.

[0066] Step 3, transfer the solution B in step 2 to a stainless steel reactor lined with polytetrafluoroethylene, put it in an oven with a programmed cooling function, set the temperature to 170°C, and the time to 76 hours.

[0067] Step 4, after the reaction kettle is slowly cooled to room temperature, it is taken out, and the product is separated by suction filtration and washing with DMF solution, and the product is in the form of blue-black blocks.

[0068] Step 5, placing the product obtained by filtration into a 50° C. vacuum drying oven, drying for 16 h, and dry grinding to obtain a blue-black powder.

[0069] Detailed description of the attached drawings:

[0070] like Figure 2 As shown, the transition metal (Cu 2+ ) The XRD diffraction pattern of the HZIF-3 framework photothermal material doped with transition metal ions has a good comparison with the XRD curve of the HZIF-3 crystal without transition metal ions, which proves the successful synthesis of the HZIF-3 framework photothermal material doped with transition metal ions.

[0071] like Figure 3 As shown, Cu 2+ SEM image of doped HZIF-3 crystal. It can be seen from the figure that the doping of transition metal ions does not change the original morphology of the crystal and each element is evenly loaded on the crystal surface.

[0072] like Figure 4 As shown, Cu 2+The surface infrared image of the doped HZIF-3 photothermal powder material was irradiated by a xenon lamp for 10 minutes with a light intensity of 1 sun. When the light was irradiated for 50 seconds, the surface temperature of the sample rose to 60°C, with the fastest heating rate. During the period of 100s-300s, the heating rate slowed down, and the maximum temperature of 90°C was reached at 220s. After the xenon lamp was turned off, the temperature dropped rapidly within 20s to 70°C. After that, the sample cooled down slowly and reached room temperature at 800s, indicating that the sample has good photothermal conversion ability, can rise to the maximum temperature in a short time and remain stable, and can also drop to room temperature in a short time after turning off the light.

[0073] like Figure 5 As shown, Cu 2+ The temperature change curve of the doped HZIF-3 photothermal powder material under xenon lamp irradiation for 10 minutes and the light intensity is 1 sun. At the beginning of the illumination, the temperature rises rapidly from 25℃ to 65℃ in 0-60s. During 60s-150s, the temperature increase decreases slightly, from 65℃ to 85℃. After 200s, the temperature rises very slowly. At 380s, the temperature of the target sample reaches 90℃. In the following time, the temperature tends to be stable.

[0074] like Figure 6 As shown, Cu 2+ The cyclic photothermal performance test curve of the doped HZIF-3 photothermal powder material. The photothermal material was tested 10 times under one sun intensity. As time goes by, the photothermal performance of the material tends to be stable, and the temperature can still rise to 90°C.

[0075] like Figure 7 As shown, Cu 2+ Absorption diagram of doped HZIF-3 photothermal powder material in the ultraviolet, visible and near-infrared regions. 2+ The absorbance of the samples after treatment increased in the near-infrared range of 1000-2500nm, indicating that doping transition metal ions into the HZIF-3 framework is beneficial to improving the absorbance of the material, thereby improving the photothermal conversion capacity of the powder material.

[0076] The synthesis principle of the key steps in the present invention is:

[0077] (I) A simple one-step solvothermal method was used to synthesize a three-dimensional hybrid zeolite imidazole framework doped with transition metal ions. During the solvothermal process, transition metal ions (Cu 2+ 、Co 2+ 、Ni 2+ , Mn 2+) can change the energy band structure of the framework, thereby broadening the light absorption range of the material. The intrinsic dd transition of transition metal ions can introduce additional photothermal conversion modules, further improving the photothermal performance of the material.

[0078] (ii) It is easy to adjust the reaction environment atmosphere under solvent thermal conditions, which is convenient for the synthesis of low-valent, intermediate-valent and special-valent compounds, and can make metal ions uniformly doped. The synthesis process consumes low energy and reduces agglomeration.

Claims

1. A method for preparing a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material, characterized in that: The specific steps are as follows: Step 1, weighing zinc citrate dihydrate, molybdic acid and 2-methylbenzimidazole, dissolving the raw materials in N,N-dimethylformamide solution, and stirring thoroughly to obtain solution A; Step 2, adding acetate to solution A respectively, mixing and stirring to obtain solution B containing transition metal ions; Step 3, transfer the solution B in step 2 to a stainless steel reactor with a polytetrafluoroethylene liner, place it in an oven with a programmed cooling function, adjust the temperature to 160° C. to 170° C., and keep it for 72 h to 76 h; Step 4, after the reaction kettle is slowly cooled to room temperature, it is taken out and the product is separated by suction filtration and washing; Step 5, placing the product obtained by filtration into a vacuum drying oven at 50° C. to 60° C., drying for 12 h to 16 h, and drying and grinding to obtain the photothermal material.

2. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 1, characterized in that: In step 1, the molar ratio of zinc citrate dihydrate, molybdic acid and 2-methylbenzimidazole is 1:11:6; The ratio of the total mass of the zinc citrate dihydrate, molybdic acid, and 2-methylbenzimidazole to N,N-dimethylformamide in step 1 is 0.65-0.7 g: 5-8 mL.

3. According to the method for preparing a transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 1, the stirring time in step 1 is 20 min-60 min.

4. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 1, characterized in that: The molar ratio of zinc citrate dihydrate to metal acetate in step 2 is 3:

1.

5. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 2, characterized in that: In step 2, the oven temperature is set at 140°C-180°C for 60h-80h; the heating rate of the oven is 3-5°C / min.

6. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 2, characterized in that: The acetate in step 2 is any one of copper acetate, cobalt acetate, nickel acetate and manganese acetate.

7. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 2, characterized in that: The solution used in the suction filtration and washing operation in step 3 is a DMF solution.

8. The method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to claim 2, characterized in that: The temperature range of the vacuum drying oven in step 4 is 40-80°C and the time is 8-20h.

9. A transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material, characterized in that: The material is prepared by the method for preparing the transition metal-doped three-dimensional hybrid zeolite imidazole framework photothermal material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Synthesizing method of zeolite-like hybrid metal imidazole framework compound

    CN103012499A

  • Macroscopic quantity preparation method and morphology control method of hybrid zeolite imidazole framework materials

    CN110372872A

  • Zinc-molybdenum bimetal organic framework multilevel structure material and preparation method thereof

    CN110776650A